2021
DOI: 10.1039/d1cc00118c
|View full text |Cite
|
Sign up to set email alerts
|

Cell-specific activation of gemcitabine by endogenous H2S stimulation and tracking through simultaneous fluorescence turn-on

Abstract: Endogenous H2S-driven theranostic H2S-Gem have been invented. The theranostic prodrug H2S-Gem is selectively activated in cancer cells, releasing active gemcitabine with a simultaneous fluorescence turn-on. H2S-Gem selectively inhibited cancer cell...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Accordingly, a bioreversible linkage (e.g., the GSH trigger, i.e., discussed in this review) attached to the self‐immolating spacer can be utilized to facilitate the connection of a broad range of tertiary and heteroaryl amine‐containing drugs for prodrug‐based therapeutic interventions. Moreover, for the vast majority of drugs lacking intrinsic fluorescent properties, the incorporation of self‐immolating spacers that exhibit fluorescence upon activation represents a widely employed strategy 82,235–239 . Nonetheless, a significant challenge arises from the suboptimal performance of these commonly used self‐immolating spacer groups in vivo imaging, owing to their emission wavelengths typically falling below 500 nm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, a bioreversible linkage (e.g., the GSH trigger, i.e., discussed in this review) attached to the self‐immolating spacer can be utilized to facilitate the connection of a broad range of tertiary and heteroaryl amine‐containing drugs for prodrug‐based therapeutic interventions. Moreover, for the vast majority of drugs lacking intrinsic fluorescent properties, the incorporation of self‐immolating spacers that exhibit fluorescence upon activation represents a widely employed strategy 82,235–239 . Nonetheless, a significant challenge arises from the suboptimal performance of these commonly used self‐immolating spacer groups in vivo imaging, owing to their emission wavelengths typically falling below 500 nm.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, for the vast majority of drugs lacking intrinsic fluorescent properties, the incorporation of self-immolating spacers that exhibit fluorescence upon activation represents a widely employed strategy. 82,[235][236][237][238][239] Nonetheless, a significant challenge arises from the suboptimal performance of these commonly used self-immolating spacer groups in vivo imaging, owing to their emission wavelengths typically falling below 500 nm. Hence, the quest for self-immolating moieties emitting within the NIR region becomes particularly imperative.…”
Section: F I G R E 21mentioning
confidence: 99%
“…Herein, we report an azide‐containing naphthalimide derivative that can serve as a fluorescence turn‐on Probe 1 for H 2 S in aqueous condition (pH 7.4 PBS solution 10 mM including 40% of dimethyl sulfoxide [DMSO], 37°C). As illustrated in Scheme 1, the azide group of Probe 1 can be reduced to a primary amine by H 2 S to produce 4‐aminonaphthalimide derivative 2 and simultaneously exhibit a fluorescent turn‐on driven by intramolecular charge transfer (ICT) 12–15 . Additionally, in the presence of H 2 S, Probe 1 may display a chromogenic change from colorless to yellow.…”
Section: Methodsmentioning
confidence: 99%
“…As illustrated in Scheme 1, the azide group of Probe 1 can be reduced to a primary amine by H 2 S to produce 4-aminonaphthalimide derivative 2 and simultaneously exhibit a fluorescent turn-on driven by intramolecular charge transfer (ICT). [12][13][14][15] Additionally, in the presence of H 2 S, Probe 1 may display a chromogenic change from colorless to yellow.…”
mentioning
confidence: 99%
“…Maiti et al reported a GEM-coumarin conjugate that could be selectively activated by the endogenous H 2 S of cancer cells to release drug and fluorescence-enhancing coumarin. 8 Nevertheless, these current approaches are still associated with limitations, such as some prodrug molecules lack targeting, small molecule prodrugs have high blood clearance and vascular permeability compared to nanodrugs, and the addition of fluorophores to nonfluorescent drugs may alter their intracellular distribution. Therefore, designing a new nanodrug delivery system for efficient targeted delivery and the real-time monitoring of GEM is essential to improving its chemotherapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%